PREPARING FUTURE LEADER OF ANTI-CORRUPTION - Khamam Khosiin Khamam Khosiin (Journal of English Education and Linguistics, 2020)
Cultivating Islamic values ​​from an since early stage such as Amanah, Iffah, Haya’ Iqtishad, and Qana’ah believed to be able to be a person who has berakhlakul karimah , Honest, trustworthy, respectful, open, shy, thrifty and always thankfull.By cultivating these values, it is hoped that our leaders will be prioritized, so he is able to future leaders who are anti-corruption.